The Driving Factors of Customers' Intentions to Use Micro Waqf Bank Financing: A Behavioral and Religiosity Approach - Fauziah, Fauziah; Hanis, Rianda (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Bank Waqaf Mikro (BWM) is a sharia-based microfinance institution whose existence is needed by the community. The basic concept of the BWM is to develop entrepreneurship among productive poor people. The BWM disburses financing which plays a very important role in encouraging the development of productive poor people's businesses. Due to the importance of the existence of the BWM, this research focuses on how to maintain the sustainability of this institution, by studying the contributor to the formation of customer intent to use BWM financing. This research uses the Theory of Planned Behavior (TPB) approach by involving the internal and external environment reflected in attitude/ATT, subjective norms/SN, and perceived behavioral control/PBC. In addition, this research involved the Religiosity variable (RG) as a moderating variable or reinforcement of each TPB variable. The results show that internal factors (attitude/ATT) influence customers to use financing services provided by the BWM. Meanwhile, external factors reflected in the perceived behavioral control or the ease of accessing the BWM financing products are important motivators for customers, supported by instilled religious values that can strengthen customer intent to use BWM financing products. Thus, the ATT and PBC variables have a positive and significant effect on customer intent (INT) with the RG variable proven to moderate (strengthen) the relationship between the ATT and the PBC variables.